Targeting mTOR in Pancreatic Ductal Adenocarcinoma - Iriana, Sentia; Ahmed, Shahzad; Gong, Jun; Annamalai, Alagappan Anand; Tuli, Richard; Hendifar, Andrew Eugene (Frontiers in Oncology, 2016)
Treatment options for advanced pancreatic ductal adenocarcinoma (PDAC) are limited, however, new therapies targeting specific tumor-related molecular characteristics may help certain patient cohorts. Emerging preclinical data has shown that inhibition of mechanistic target of rapamycin (mTOR) in specific KRAS-dependent PDAC subtypes leads to inhibition of tumorigenesis in vitro as well as in vivo. Early phase II studies of mono-mTOR inhibition have not shown promise. However, studies have shown that combined inhibition of multiple steps along the mTOR signaling pathway may lead to sustained responses by targeting mechanisms of tumor resistance. Coordinated inhibition of mTOR along with specific KRAS-dependent mutations in molecularly defined PDAC subpopulations may offer a viable alternative for treatment in the future.